Stolthet, fordom og en ydmyk Henrik: En kulturhistorisk analyse av kategorier, metaforer og ugress - Egeberg, Solveig Myrstad Wøllo (Tidsskrift for kulturforskning, 2025)
This article discusses the metaphorical and conceptual understanding of weeds as a category of plants, a topic that is unexplored in humanities departments in Norway. The literary discourse surrounding the Norwegian agronomist and botanist Emil Korsmo from 1896 to 1931 is analysed. Using metaphors and descriptive terms, Korsmo defined an understanding of weeds as the dirty enemies of the farmer, to be eradicated at all costs. Although Korsmo’s definition of a weed, «a plant you don’t intend to grow here», acknowledges the relative and human nature of weed categorization, the relative identity of weeds are overshadowed by the metaphorical system of «weeds are polluted» and «weeds are enemies». In Korsmo’s rethoric, weeds as untidy and unsightly, pathogenic, and dangerous plants are emphasized, while weeds as a category of plants shaped by humans, with possibilities for transformation and redefinition, are concealed. This article illustrates the consequences and power of categorising weeds through the plant Blitum bonus-henricus, which, despite being on the Norway’s Red List of endangered species, is still perceived as a weed to be eliminated. The main argument is that the categorisation and linguistic metaphors used to order and make sense of the world, ultimately has material consequences.